Trend and research focus on Problem-Based Learning and learning outcome in the world: A bibliometric analysis - Agus Fatkhurohman Handoyo; Ade Sobandi; Widhi Aryo Bimo (Inovasi Kurikulum)
A problem-based learning approach is a learning approach that is student-centered, allowing them to confront real-world problems, encouraging critical thinking, collaboration and problem solving. This research aims to investigate several key aspects related to PBL and learning outcomes at a global level and generate in-depth insights into research trends and focuses related to problem-based learning (PBL) approaches and learning outcomes. through bibliometric analysis. From 1132 Scopus database articles, after going through the selection process there were 742 articles. It was found that interest and research focus on this topic has increased significantly in recent years, reflecting the importance of PBL in developing students' critical and collaborative skills. The importance of developing valid and reliable educational measurement tools to measure learning outcomes. The importance of international collaboration in enriching understanding of PBL and learning outcomes. Human factors, such as student characteristics, were found to be important in designing a PBL curriculum that is responsive to student needs. These findings provide guidance for future research directions, highlighting the innovative potential in PBL development. In conclusion, these results and discussion provide a strong foundation for the development of education oriented towards effective learning outcomes in the modern era.